Depicting the exemplary knowledge of microbial exopolysaccharides in a nutshell. (October 2019) - Shukla, Arpit; Mehta, Krina; Parmar, Jignesh; Pandya, Jaimin; Saraf, Meenu
Graphical abstract: Abstract: Microorganisms can utilize an extensive assortment of carbon and nitrogen sources as well as various added nutrients ranging from simple to complex. Depending on the microbe and the metabolic pathway they undergo, these nutrients are efficiently converted into complex and diverse biopolymers with varied physico-chemical properties. Exopolysaccharides (EPS) are biopolymers that primarily contain- carbohydrates. The extensively studied EPS producing bacteria include Leuconostoc mesenteroides, Xanthomonas campestris, Acinetobacter calcoaceticus, Lactobacillus sp . and Alkaligenes sp. However, some prominent fungal exopolysaccharides produced by Aspergillus niger, Lentinula edodes, Fusarium solani, Botryosphaeria rhodina, Coriolus versicolor have also been put to commercial use. While the microbes may vary substantially in their physiology, the production of EPS depends largely on the optimization of the growth by varying various parameters influencing growth and the meticulous designing of its production media. EPS acts as an invaluable asset for the producing microbe by providing manifold benefits including but not restricted to: protection against- desiccation, starvation, phagocytosis, UV radiation, environmental stress and water retention. Being eco-friendly and biodegradable, major microbial EPS such as; dextran, xanthan, alginate, hyaluronan, pullulan, chitosan and lentinam have found numerous vital applications in pharmaceutical, agriculture, food and cosmetics industries. This review provides an inclusive insight into the world of microbial exopolysaccharides covering its major aspects, namely- its types, biosynthesis and the factors that influence its production along with various techniques used for its recovery and further characterization. Special emphasis is placed on the applications of EPS in various large-scale commercial and industrial sectors.